Pengembangan Badan Usaha Milik Desa (Bumdes) Berbasis Potensi Lokal Sebagai Penggerak Ekonomi Desa Pangkah Wetan Kec. Ujung Pangkah Kabupaten Gresik - Sri Umiyati; Soenyono S; Edi Suhardono; Dian Mulawarmanti; Siswo Hadi Sumantri; Sulistiyanto S; Arfah A; Budi Rianto; Arie Ambarwati; Agus Wahyudi (Yayasan Daarul Huda Kruengmane, 2023)
This community service program is carried out in Pangkah Wetan Village, Ujung Pangkah District, Gresik Regency. In the context of developing a Village-Owned Enterprise (Bumdes) based on local potential as an economic driver of Pangkah Wetan Village, Ujung Pangkah District, Gresik Regency, it is possible that some problems that arise with partners or parties involved are: 1. Lack of Environmental Awareness: 2. Unsynchronized goals: 3.Budget Limitations: 4. Lack of Coordination: 5. Disagreement in Planning. 6. Low Community Involvement: 7. Technical and Environmental Constraints: 8. Policy Changes: 9. Difficulty Coordinating with Local Communities: 10. Unclear Roles and Responsibilities. In addressing these issues, good communication, collaboration, flexibility and mutual commitment are essential. Through open dialogue and constructive problem solving, many obstacles can be overcome, and sustainable and beneficial BUMDes development can be realized.